Implementation of a peer support intervention to promote the detection, reporting and management of adverse drug reactions in people living with HIV in Uganda: a protocol for a quasi-experimental study - Freddy Eric Kitutu; Victoria Nambasa; Ronald Kiguba; Helen Byomire Ndagije; Cordelia Katureebe; Phil Tregunno; Kendal Harrison; Jacquellyn Nambi Ssanyu; Henry Zakumumpa; Corinne S Merle; Stella Maris Nanyonga; Marie-Eve Raguenaud (BMJ Open)
Introduction Patients have contributed <1% of spontaneous adverse drug reaction (ADR) reports in Uganda’s pharmacovigilance database. Peer support combined with mobile technologies could empower people living with HIV (PLHIV) to report ADRs and improve ADR management through linkage to care. We seek to test the feasibility and effect of a peer support intervention on ADR reporting by PLHIV receiving combination antiretroviral therapy (cART) in Uganda; identify barriers and facilitators to the intervention; and characterise ADR reporting and management.Methods and analysis This is a quasi-experimental study to be implemented over 4 months at 12 intervention and 12 comparison cART sites from four geographical regions of Uganda. Per region, two blocks each with a tertiary, secondary and primary care cART site will be selected by simple random sampling. Blocks per region will be randomly assigned to intervention and comparison arms.Study units will include cART sites and PLHIV receiving cART. PLHIV at intervention sites will be assigned to peer supporters to empower them to report ADRs directly to the National Pharmacovigilance Centre (NPC). Peer supporters will be expert clients from among PLHIV and/or recognised community health workers.Direct patient reporting of ADRs to NPC will leverage the Med Safety App and toll-free unstructured supplementary service data interface to augment traditional pharmacovigilance methods.The primary outcomes are attrition rate measured by number of study participants who remain in the study until the end of follow-up at 4 months; and number of ADR reports submitted to NPC by PLHIV as measured by questionnaire and data abstraction from the national pharmacovigilance database at baseline and 4 months.Ethics and dissemination The study received ethical approval from: School of Health Sciences Research and Ethics Committee at Makerere University (MAKSHSREC-2020-64) and Uganda National Council for Science and Technology (HS1206ES). Results will be shared with PLHIV, policy-makers, the public and academia.Trial registration number ISRCTN75989485.